Agribusiness Indicators : Synthesis Report - World Bank (Washington, DC, 2014)
The need for countries in Sub-Saharan Africa to build more productive, modern, and market-oriented farming sectors is one of our most pressing development challenges. In coming years, African agriculture will have to increase food production and expand and intensify value chains in order to meet changing demand on the part of a rapidly expanding and urbanizing consumer base. The process of doing this will enable African countries to begin pushing back against their currently growing reliance on food imports. An essential precondition for bringing this transformation to pass is to increase and improve the information on which farmers and agribusinesses base their production and investment decisions, and on which public sector institutions base their policies. The purpose of the Agribusiness Indicators (ABIs) Project is to provide this kind of empirical information in the form of a series of metrics and indicators that can be used to measure change over time and to make direct comparisons between countries, especially policy makers. These indicators will be used to inform policy dialogue, including dialogue between representatives of the private and public sectors. It will provide a common framework of reference with which to communicate their respective concerns, priorities, and intentions. This will facilitate better communication that leads to constructive interaction between public officials, farmers producer organizations, private investors, civil society organizations (CSOs), and others. Ultimately, it will be their decisions that determine the course of agricultural development and commercialization in their respective countries. The Agribusiness Indicators are intended to furnish them with information from sources within both the private and public sectors which can be cross-referenced and correlated. This type of information has generally not been available in the past. Some of the indicators are particularly useful in revealing the attributes of countries with policy portfolios that are supportive of agribusiness investment.